The Gender Euphoria Scale (GES): a protocol for developing and validating a tool to measure gender euphoria in transgender and gender diverse individuals - Blacklock, C. A.; Tollit, M. A.; Pace, C. C.; Elphinstone, B.; Pang, K. C.; Buzwell, S. (Frontiers in Psychology, 2024)
Background: Gender euphoria (i.e., a positive feeling associated with one's gender identity, expression, or affirmation) is widely discussed among transgender and gender diverse (hereafter referred to as trans) individuals. However, as a construct, gender euphoria has never been formally measured and has rarely been empirically studied. Hence, this protocol paper illustrates our process for developing and validating a new tool to measure gender euphoria, known as the Gender Euphoria Scale (GES), for use with trans populations. Methods: Deductive methods including findings from previous research and a review of existing measures, together with inductive methods such as expert feedback and focus groups with trans individuals, were used to generate a preliminary item pool for the GES. Pilot testing with trans community members and mental health clinicians was then used to refine items and develop a preliminary scale. Participants involved in an ongoing longitudinal study (TRANSform) were invited to complete the scale alongside measures of personality and gender factors to assess validity. Participants were then invited to complete the scale two weeks after initial completion to assess the test-retest reliability of the scale. The next stage in the scale development process will be to examine the dimensionality of the GES using exploratory factor analytic techniques. The scale will then be assessed for internal consistency, temporal stability, discriminant validity, and convergent validity.This paper outlines the development and characterisation of a novel tool to measure gender euphoria for the first time. The GES will facilitate research opportunities to better understand the nature of gender euphoria and its influences and may be used clinically to examine relationships between gender euphoria and gender affirming interventions. Hence, we expect the GES to make a significant contribution to both research and clinical practice with trans communities.